Crop wild relatives of Kaliningrad Province recommended for in situ conservation - L. Yu. Shipilina (Труды по прикладной ботанике, генетике и селекции)
Background. Preservation of the entire genetic diversity of the world’s flora is indispensable to the deployment of breeding practice aimed at development and improvement of the existing economically useful plant species and varieties. The in situ conservation approach is recognized as the topmost priority. Therefore, a study of crop wild relatives (CWR) in Kaliningrad Province appears vital to identify the most vulnerable species and enhance their in situ conservation.Materials and methods. Crop wild relatives occurring in Kaliningrad Province were the research target. The WIR and LE herbarium collections, published data, and results of VIR’s plant explorations undertaken in 1974 and 1983 served as the material for the research. Plant species included in the Red Data Books of Kaliningrad Province, Lithuania, Estonia, Poland, etc. were analyzed, and the data from open databases (GBIF, CWR, ILDIS, etc.) and AgroAtlas maps were employed. CWR requiring special conservation measures were identified.Results and conclusions. Kaliningrad Province, Russia, is home to 324 species of CWR. Natural habitats of the 6 most vulnerable plant species were mapped: Vicia dumetorum L., Trifolium rubens L., Chrisaspis spadiceum L., Elytrigia juncea (L.) Nevski, Phleum phleoides (L.) H. Karst., and Allium vineale L. These species fall under the 1st vulnerability category.